1996
DOI: 10.1046/j.1523-1739.1996.10010188.x
|View full text |Cite
|
Sign up to set email alerts
|

The Early Development of Forest Fragmentation Effects on Birds

Abstract: The early development of forest fragmentation effects on forest organisms is poorly understood partly because most fragmentation studies have been done in agricultural or suburban landscapes, long after the onset of fragmentation. We develop a temporal model of forest fragmentation effects on densities of forest‐breeding birds and provide data from an active industrial forest landscape to test the model. The model and our empirical data indicate that densities of several forest‐dwelling bird species can increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
5
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(134 citation statements)
references
References 42 publications
7
121
5
1
Order By: Relevance
“…In the short term, crowding effects (Bierregaard et al, 1992 ;Debinski & Holt, 2000) occur when organisms that survive the immediate process of habitat loss are concentrated into the much smaller amount of remaining habitat, thereby increasing population densities and species richness within habitat fragments (Collinge & Forman, 1998). For example, this displacement phenomenon (Hagan, Haegen & McKinley, 1996) occurred almost immediately following habitat loss in Amazonian bird communities (Lovejoy et al, 1986) and in grassland invertebrates of the western USA (Collinge & Forman, 1998), but was not observed at all for Lumholtz's tree kangaroo, Dendrolagus lumholtzi, following deforestation in tropical northern Australian (Newell, 1999). In the latter species, individuals exhibited strong site fidelity and chose to remain in the deforested, degraded habitat rather than move to nearby continuous forest (Newell, 1999).…”
Section: Confounding Factors In the Detection Of Fragmentation Imentioning
confidence: 99%
“…In the short term, crowding effects (Bierregaard et al, 1992 ;Debinski & Holt, 2000) occur when organisms that survive the immediate process of habitat loss are concentrated into the much smaller amount of remaining habitat, thereby increasing population densities and species richness within habitat fragments (Collinge & Forman, 1998). For example, this displacement phenomenon (Hagan, Haegen & McKinley, 1996) occurred almost immediately following habitat loss in Amazonian bird communities (Lovejoy et al, 1986) and in grassland invertebrates of the western USA (Collinge & Forman, 1998), but was not observed at all for Lumholtz's tree kangaroo, Dendrolagus lumholtzi, following deforestation in tropical northern Australian (Newell, 1999). In the latter species, individuals exhibited strong site fidelity and chose to remain in the deforested, degraded habitat rather than move to nearby continuous forest (Newell, 1999).…”
Section: Confounding Factors In the Detection Of Fragmentation Imentioning
confidence: 99%
“…Schmiegelow et al 1997) has demonstrated that in the first year or two after winter-harvesting, migratory birds often pack into remaining forest stands resulting in an unnaturally high density. In some cases this has been shown to result in negative effects on the nesting success of birds in remnant stands because of increased resource competition (Hagan et al 1996). The same phenomena could occur in stands directly adjacent to summer harvested areas within the year of harvest but has not been tested to the best of our knowledge.…”
Section: Loss Of Nests: a Recruitment Perspectivementioning
confidence: 97%
“…The operation of other processes could also be suspected. For example, a severe reduction of food in ranches could lead to crowding effects in the protected area, as has been suggested for other taxa after substantial habitat removal (Hagan et al 1996). Finally, similar monitoring approaches could be useful to manage the widespread predatorlivestock conflict, as long as predator populations occupy refuges or constitute conservation targets (Herfindal et al 2005;Fleming et al 2006).…”
Section: Management Implicationsmentioning
confidence: 99%